Intraspecific structure of Myotis petax Hollister, 1912 (Chiroptera: Vespertilionidae) based on mitochondrial DNA and morphological data - Uliana V. Gorobeyko; Denis V. Kazakov; Anastasia A. Kadetova; Irina N. Sheremetyeva; Valentin Yu. Guskov; Irina V. Kartavtseva; Nikolai E. Dokuchaev; Evgeniy S. Zakharov; Sergei V. Kruskop (Vertebrate Zoology)
Abstract Myotis petax is a common and widespread Asian bat species, whose intraspecific sequence variability remains poorly understood. In this work we analyzed the variability of the mitochondrial control region and craniometric measurements for an extensive sample set originating from the entire species range. This made it possible to identify the main genetic lineages and to compare their distribution with the morphological groups. From our investigations, we found that the prevalent genetic lineages, namely, “Siberia,” “Amur,” and “Okhotsk,” appear to be connected to large river systems. The cohabitation of various genetic lineages occurs only in territories where different river basins are connected, such as the Primorsky Territory, Khabarovsk Territory, Transbaikalia Territory, and Mongolia. Moreover, we discovered that the five morphological groups (Siberia, Okhotsk, Amur, Kunashir, and Korea) are partially correlated with previously identified genetic lineages and subspecies. However, M. p. petax and M. p. loukashkini were the only two out of the five subspecies that could be well-defined using specific mtDNA sequences and morphological descriptions. Nonetheless, the subspecies M. p. ussuriensis does not have a distinct genetic lineage to allow for their classification. Notably, a specific mix of morphological group and a genetic lineage characterize the “Amurian morphological form,” which may support its validity as a subspecies rank. That notwithstanding, more information is needed to fully unravel the intraspecific structure of M. petax in the southern Far East and potential contact zones of diverse forms.